Environmental sustainability reporting: a systematic and bibliometric review of two decades of research - Elena Rivo-López; Mónica Villanueva-Villar; Carmen Pardo-López; Mónica Cortés-García (Future Business Journal)
Abstract Environmental sustainability is a global concern for governments, companies, investors and consumers. The efforts made by companies to improve sustainability are reflected in their reports. In this sense, the new European Directive on corporate sustainability reporting pushes for ESG indicators to become key information for managers. This study presents a hybrid literature review that combines bibliometric mapping with a structured review of the most influential contributions on environmental sustainability reporting. The objective is to review the publications to identify academic trends, relevance, relationships and methodological advances on the subject. A total of 257 articles on environmental sustainability reporting were located and analysed from the Scopus and WOS databases from 2005 to May 2024. The paper grouped environmental sustainability reporting research into four clusters: sustainability accounting, sustainability reporting and governance, environmental performance and environmental disclosure. The in-depth review of the most cited contributions highlights the influence of corporate governance, organizational culture and firm characteristics on sustainability reporting practices. This article offers a synthesis of the academic literature and identifies key trends and research gaps to guide future studies and support organizations in enhancing the quality, transparency and strategic value of their environmental sustainability reports.